The idea of God in the heritage of the Ukrainian philosophers (40-th years of XIX-50-th years of XX centuries): меthodological contradictons and prospects - Timenyk Zуnovij (Skhid, 2016)
In this article the author considers the idea of God and the system of His names in the context of the structure of a human being and the universe on the basis of the analysis of the Ukrainian thinkers of 40th years of XIX - 50th years of XX centuries works. The author also stresses that from the view’s history of philosophy the use of etymological, semantic and evolutionary approaches allow stressing that the idea of God contains Hebrew and ancient Greek meanings and in the process of becoming undergo changes. The author also shows that the given idea helped to form interreligious communications and analyses interdisciplinary character of the idea of God, which was manifested in its philosophical and religious synthesis. The author stresses: Ukrainian thinkers as N. Berdiаiev, S. Bulhakov, A. Giliarov, S. Gogots’ky, Metr. Ilarion [Ohiyenko], O. Kozlov, I. Maksymovych, O. Novyts’ky and others were introduced the new approaches to comprehending of the idea of God on the border of interreligious communications and interdisciplinary space. Since those thinkers consider the possibility of typification of the common and the different in the spiritual life of the representatives of those religions.